2019
DOI: 10.1016/j.knee.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Preservation vs. resection of the infrapatellar fat pad during total knee arthroplasty part II: A systematic review of published evidence

Abstract: This is a repository copy of Preservation vs. resection of the infrapatellar fat pad during total knee arthroplasty part II: A systematic review of published evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…More recently, a systematic review reported that IFP preservation leads to a reduction in long-term knee pain [41]. However, there is a need of level one randomized controlled trials, which would shed light on this issue [41, 42].…”
Section: The Role Of the Ifp-synovial Membrane As A Functional Unimentioning
confidence: 99%
“…More recently, a systematic review reported that IFP preservation leads to a reduction in long-term knee pain [41]. However, there is a need of level one randomized controlled trials, which would shed light on this issue [41, 42].…”
Section: The Role Of the Ifp-synovial Membrane As A Functional Unimentioning
confidence: 99%
“…• The retro-patellar bursa and Infra Patellar Fat Pad (I.P.F.P.) are preserved, since they act as a hydraulic shock absorber, filling the anterior compartment [12,19,20]. The I.P.F.P.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies described the blinding of outcome assessment, and three studies described the blinding of participants and personnel. All studies retained complete outcome data, avoided selective reporting, and had an unclear risk of other bias analysis [21] comparing IPFP resection and IPFP preservation in primary TKA. However, the inclusion criteria of the previous meta-analyses included only 2 RCTs and five retrospective cohort studies design, which are potentially subject to selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first meta-analysis of only RCTs comparing IPFP resection and IPFP preservation in primary TKA. We only found one meta-analysis [ 21 ] comparing IPFP resection and IPFP preservation in primary TKA. However, the inclusion criteria of the previous meta-analyses included only 2 RCTs and five retrospective cohort studies design, which are potentially subject to selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation